Intellectual Property Animasi Di Indonesia Dalam Buku Katalog Nganimasi Indonesia - Santoso, Bambang Gunawan (Institut Bisnis dan Teknologi Indonesia, 2018)
IP or Intellectual Property refers to the creation of the mind; invention; literary and artistic works; symbols, names and drawings used in the trade. Intellectual property rights (HKI) are rights granted to IP creators, and include trademarks, copyrights, patents, industrial design rights, and in some trade secret jurisdictions. Works of art including music and literature, as well as discoveries, words, phrases, symbols and designs can all be protected as intellectual property or IP. Until now the catalog book